Pengaruh Laju Aliran Volume Chilled Water Terhadap NTU pada FCU Sistem AC Jenis Water Chiller - I Made Rasta (Jurnal Teknik Mesin (Sinta 3), 2007)
Water Chiller Air Conditioning (AC) is an air conditioning system that has ability for cooling more than one room. The water chiller AC have two cycles consist of primary and secondary cycles. In the primary cycle, refrigerant is used as working fluid while in the secondary cycle, the water is used as working fluid. To determine the heat absorbed by water, it can be done by analyzing NTU (Number of Transfer Unit) of the water chiller system. The variation of the chilled water volume rate applied in this research was from 13 l/min to 5 l/min, with the interval of 0.5 l/min. As a result, it was founded that the maximum value of NTU was 2.01, at chilled water volume rate of 12 l/min. Below that chilled water volume rate, values of NTU would decrease and stable. It can be concluded that the volume rate of chilled water influenced the value of NTU in the FCU (Fan Coil Unit) of the water chiller AC system. Abstract in Bahasa Indoensia: AC water chiller merupakan alat pengkondisian udara yang dapat mengkondisikan udara lebih dari satu ruangan untuk satu perangkat AC, karena sistem AC water chlller terdiri dari dua siklus yaitu siklus primer dan siklus sekunder. Pada siklus primer yang bertindak sebagai fluida kerja adalah refrigeran dan pada siklus sekunder yang bertindak sebagai fluida kerja adalah air. Untuk mengetahui penyerapan panas terjadi secara maksimal oleh air dapat dilakukan dengan menganalisa NTU dari sistem water chiller tersebut. Variasi laju aliran volume dilakukan dari 13 ltr/mnt sampai 5 ltr/mnt dengan selisih 0,5 ltr/mnt setiap pengujian. .Dari hasil pengolahan data dan analisa grafik didapat bahwa NTU terbesar yaitu 2,01 dicapai pada laju aliran volume 12 ltr/mnt yaitu sebesar 2,01, kemudian turun dan stabil. Jadi laju aliran volume chilled water berpengaruh terhadap NTU pada sisi FCU dari sistem water chiller. Kata kunci: NTU, laju aliran volume, air pendingin, AC water chiller.